Competitive endogenous RNA network: potential implication for systemic lupus erythematosus. (3rd June 2017) - Li, Lian-Ju; Zhao, Wei; Tao, Sha-Sha; Leng, Rui-Xue; Fan, Yin-Guang; Pan, Hai-Feng; Ye, Dong-Qing
ABSTRACT: Introduction : Competitive endogenous RNA (ceRNA) hypothesis proposes that RNA transcripts, both coding and non-coding, crosstalk with and coregulate each other using microRNA response elements (MREs). CeRNA analysis tremendously expands functional information of coding and non-coding RNAs. Mounting evidence have shown that various types of RNAs, including pseudogenes, long non-coding RNAs, circular RNAs, and messenger RNAs, can function as ceRNAs in distinct physiological and pathophysiological states. Many validated ceRNA pairs participate in the initiation and progression of cancers, and systemic ceRNA network analyses revealing potential of ceRNAs in diagnosis, therapy, and prognosis of cancers have also been performed. Areas covered : This review concisely introduces ceRNA hypothesis and characteristics of ceRNA regulations. The major sections focus on representative examples of both protein coding and non-coding RNA transcripts acting as ceRNAs. CeRNA prediction programs and databases and implications of ceRNA network in cancers are then discussed. In the end, we surmise potential implications of ceRNA network for SLE. Expert opinion : The role of ceRNA network in systemic lupus erythematosus (SLE) remains undefined. We speculate that dissecting ceRNA network in SLE may help expand our comprehension of roles of transcriptome, particularly non-coding transcripts, and richen our knowledge of pathogenesis, diagnosis, and therapy of SLE.